The deadly combination of a keto diet and SGLT-2 inhibitors: A case of euglycemic ketoacidosis - Saha, Tanmoy Kumar; Mannan, Md Abdul; Khan, Md Oahidul Islam; Rahman, Sunny Isnain; Rahman, Md Ashiqur (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Diabetic ketoacidosis is an acute and serious complication of diabetes mellitus, which usually occurs in type 1 but is not uncommon in type 2 diabetes patients. It is characterized by hyperglycemia, metabolic acidosis, and ketone bodies in the blood or urine. A subgroup of patients may present without signs of hyperglycemia with normal blood glucose levels, thus posing a diagnostic challenge. Here, we report a case of a 42-year-old gentleman who presented to the emergency room and was diagnosed with euglycemic diabetic ketoacidosis 3 days after starting Empagliflozin along with a strict low-carbohydrate diet. Extensive workup failed to demonstrate any other factor, such as infection, that may have led to this complication. This article aims to raise awareness among clinicians to be aware of this diagnosis in the differentials in patients taking SGLT-2 inhibitors who are also on a strict low-carbohydrate diet. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 39-42